2010
DOI: 10.1215/03616878-2010-034
|View full text |Cite
|
Sign up to set email alerts
|

Images of Illness: How Causal Claims and Racial Associations Influence Public Preferences toward Diabetes Research Spending

Abstract: Despite the salience of health disparities in media and policy discourse, little previous research has investigated if imagery associating an illness with a certain racial group influences public perceptions. This study evaluated the influence of the media’s presentation of the causes of type 2 diabetes and its implicit racial associations on attitudes toward people with diabetes and preferences toward research spending. Survey participants who viewed an article on genetic causation or social determinants of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Small and colleagues found that people are more punitive toward identified “wrongdoers” than unidentified wrongdoers, just as Slovic and colleagues found that people are more sympathetic toward identified victims than unidentified victims. Previous research assessing the impact of personalized depictions on attitudes toward diabetes also found that presenting any image of a person with diabetes—compared to a photo of a medical device—was associated with more negative attitudes toward people with diabetes (Gollust, Lantz, & Ubel, ).…”
Section: Discussionmentioning
confidence: 97%
“…Small and colleagues found that people are more punitive toward identified “wrongdoers” than unidentified wrongdoers, just as Slovic and colleagues found that people are more sympathetic toward identified victims than unidentified victims. Previous research assessing the impact of personalized depictions on attitudes toward diabetes also found that presenting any image of a person with diabetes—compared to a photo of a medical device—was associated with more negative attitudes toward people with diabetes (Gollust, Lantz, & Ubel, ).…”
Section: Discussionmentioning
confidence: 97%
“…Some Americans attribute social conditions to personal flaws while others attribute them to societal factors, and this is strongly associated with support for policies addressing these factors (Iyengar, 1989). For example, adults were more likely to support government spending on research of DM2 after viewing an article on social determinants of DM2 compared to those viewing an article with no causal language (Gollust, Lantz, & Ubel, 2010). People’s attributions of responsibility for health disparities therefore shape support for policy, and more effective messaging to emphasize social determinants of health has potential to influence policy support (Niederdeppe, Bu, Borah, Kindig, & Robert, 2008).…”
Section: Rationale and Theoretical Underpinningsmentioning
confidence: 99%
“…Extant research on potential genre-based variations in the eliciting of (2) attitude change and emotional response paints a more mixed picture. This is because all reporting can influence attitude formation and touch audiences emotionally, but this may be as Coleman and Thorson (2002), Wilkins (2011), Gollust, Lantz, andUbel (2010), Gross (2008), Hart (2011), Kühne, Weber, and Sommer (2015), Major (2009), Major (2011), Major and Jankowski (2020), Shen et al (2012), Springer and Harwood (2015), Sun et al (2016), Waheed et al (2015) Emotions -↑ Aarøe (2011), Gross (2008), Kühne, Weber, and Sommer (2015), Major (2011), Shen et al (2012…”
Section: Audience Perceptionsmentioning
confidence: 99%
“…Macro-level Micro-level Coleman and Thorson (2002), Wilkins (2011), Gollust, Lantz, andUbel (2010), Hart (2011), Major (2009, Major and Jankowski (2020), Matthes (2009a), Sun et al (2016) much a function of issue specificities, context and individual predispositions as one of reporting styles (Iyengar 1991;Druckman and McDermott 2008). Thus, the evidence is inconclusive.…”
Section: Attribution Of Responsibilitymentioning
confidence: 99%
See 1 more Smart Citation